(untitled) (Información, cultura y sociedad, 2010)
This is an attempt to provide a panoramic view of the possible paths open to graduates in Library Science at the start of a career in research in the field. Towards that aim, reflection on theory is blended with personal experience. Following analysis and discussion of the concepts included in the title of the article, the content is set within the framework of reference of social epistemology and the concept of scientific knowledge as a social construct. The connotations associated with Librarianship, Documentation and Information Science are further refined in this context with an approach that combines historical/etymological perspectives in the light of current theoretical approaches. A table is provided for guidance with different study areas clearly marked. The options afforded by the Argentinean system for scientific research are analyzed and its weaknesses identified as the failure of institutions to provide accurate descriptions of the disciplines involved in our field, which often leads to confusion and conflict for those wishing to devote themselves to research. Three itineraries towards access to the formal system of scientific research are offered as choices: the academic track at university, the CONICET (National Council for Research in Science and Technology), and advanced studies. Five recommendations are made towards the inclusion and recognition of our discipline , the drawing of lists of experts that will sit on committees for ad-hoc evaluation and assessment, the implementation of post graduate courses of study, the enhancement and creation of doctoral programmes, and the setting up of a register of post graduate study experiences.